2000
DOI: 10.1016/s0020-1693(99)00561-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hydrophilic, amphiphilic and hydrophobic ions at a liquid/liquid interface: a molecular dynamics investigation

Abstract: We report molecular dynamics studies on the interfacial distribution of ionic species of different size, shape and topology at a water/chloroform interface: hydrophilic K + Cl − , K + SCN − and K + Pic − ions, amphiphilic ammonium NTMA + cations and farnesylphosphate FPH − anions, tetrahedral hydrophobic AsPh 4 + and BPh 4 − ions, with different counterions. Contrasted distributions are observed. The K + Cl − and K + SCN − ions sit almost exclusively in the water phase, but SCN − is less 'repelled' than Cl − b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 73 publications
4
56
1
Order By: Relevance
“…The reason has to be found in the accumulation of positively charged 222 2 + species at the interface, creating a positive potential which attracts the anions. The Cldistribution in our systems contrasts with the one observed with the more hydrophilic K+Cl-or NMetcl-systems, where all ions are "repelled" by the interface [32]. There are, however, subtle differences between the distributions of Cl-vs. r counterions simulated here (compared systems E to G and J to H).…”
Section: Concentrated Solutions Of 222 2+ With Halide Counterionscontrasting
confidence: 82%
See 2 more Smart Citations
“…The reason has to be found in the accumulation of positively charged 222 2 + species at the interface, creating a positive potential which attracts the anions. The Cldistribution in our systems contrasts with the one observed with the more hydrophilic K+Cl-or NMetcl-systems, where all ions are "repelled" by the interface [32]. There are, however, subtle differences between the distributions of Cl-vs. r counterions simulated here (compared systems E to G and J to H).…”
Section: Concentrated Solutions Of 222 2+ With Halide Counterionscontrasting
confidence: 82%
“…More surprising is the calculated surface activity of la~ge spherical s+ and s-model ions, whose radius (5 A) is close to the gyration radius of 222 [49,50]. According to simulations, smaller anions like ClO,i or quaternary ammonium NRt cations are also surface active [32], leading to a decrease in INTERFACIAL ACTIVITY OF 222 2 + 141 surface tension [51][52][53][54]. Even tetracharged tetrahedral ammonium hosts and their anion complexes are surface active, as shown by MD simulations [55], in keeping with the experimental observations of their transport properties through hydrophobic membranes [56].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, we recently found that large quasi‐“spherical” ions, like mono‐ or divalent cryptates,13 AsPh 4+, BPh 414–16 or dicarbollide anions17 adsorb at liquid–liquid interfaces (LLI), and it is interesting to test computationally whether the tetrahedral tetraammonium complexes behave similarly. These investigations extent our work on ions and complexes at LLIs 18–21. Interestingly, it was reported that L 4+ derivatives with R = CH 2 ϕ form two‐dimensional assemblies at the interface between the NaCl(001) surface and water where they complex chloride anions 10.…”
Section: Introductionsupporting
confidence: 59%
“…(28) On the other hand, hydrophilic metallic ions are "repelled" by the interface, preventing their capture by water insoluble extractants. (29) It is thus important to understand at the molecular level what happens at the liquid boundaries (30) and we report new microscopic insights into this question obtained from molecular dynamics (MD) simulations with explicit representation of the solvents and solutes.…”
Section: Introductionmentioning
confidence: 99%